Characterisation of Eubacterium cell wall: peptidoglycan structure determines arthritogenicity. Issue 3 (1st March 2001) - Zhang, X; Rimpiläinen, M; Šimelyte, E; Toivanen, P
Abstract : OBJECTIVE: To elucidate factors involved in the arthritogenicity of bacterial cell walls. METHODS: For characterisation of an arthritogenic Eubacterium aerofaciens cell wall, peptidoglycan-polysaccharide (PG-PS) polymers were isolated by removing cell wall associated proteins (CWPs), PG and PS moieties were separated, and an attempt was made to de- O -acetylate PG-PS. The cell wall of E limosum was used as a non-arthritogenic control. The chemical composition of these cell wall preparations was analysed by gas chromatography-mass spectrometry. Also, their ability to resist lysozyme degradation and to sustain experimental chronic arthritis was tested. RESULTS: The observations made with the cell wall of E aerofaciens, an anaerobic habitant of the human intestine, were compared with those reported from a pathogenic Streptococcus, showing that in both strains a complex consisting of PG-PS is required for the induction of chronic arthritis. The PS moiety most probably protects PG from enzyme degradation, allowing prolonged tissue persistence and leading to the chronic synovial inflammation. CWPs attached to PG-PS are not necessary for this function. O -Acetylation of PG, which is required for arthritogenicity of the streptococcal cell wall, seems not to be present in the arthritogenic E aerofaciens PG or only occurs to a small degree; attempts to de- O -acylate the E aerofaciens cell wall did not affect its arthritogenicity or lysozyme resistance. CONCLUSION: The results obtained indicate that the source of bacterial cell wall plays no part in the chemical or structural requirements for PG to induce chronic cell wall arthritis in the rats; the chemical structure of the PG moiety is decisive.